2010
DOI: 10.21153/jtlge2010vol1no1art547
|View full text |Cite
|
Sign up to set email alerts
|

Using successful graduates to improve the quality of undergraduate nursing programs

Abstract: This paper outlines the context and focus of the late 2008 survey of 45 early career nursing graduates working in public hospitals in an outer-urban area of Sydney who were identified by their supervisors as performing successfully. It gives an overview of the key quantitative and qualitative results for 2008 compared with the results of earlier studies of successfully performing nurses and other professionals in the first 3-5 years of their career. Based on this analysis it makes a range of recommendations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 5 publications
2
31
0
Order By: Relevance
“…both job-specific skills and generic skills, to develop an ability to read the situation and determine a suitable strategy. Scott and Yates (2002) describe this as professional capability. They discuss whether individual graduates can be 'emotionally intelligent' (graduates with higher order personal and interpersonal skills who can problem solve, think creatively, communicate, negotiate and find solutions rather than know them) and whether or not, universities have contributed to the initiation or fostering of such skills.…”
Section: Development Of Graduate Attributes During University Studiesmentioning
confidence: 99%
“…both job-specific skills and generic skills, to develop an ability to read the situation and determine a suitable strategy. Scott and Yates (2002) describe this as professional capability. They discuss whether individual graduates can be 'emotionally intelligent' (graduates with higher order personal and interpersonal skills who can problem solve, think creatively, communicate, negotiate and find solutions rather than know them) and whether or not, universities have contributed to the initiation or fostering of such skills.…”
Section: Development Of Graduate Attributes During University Studiesmentioning
confidence: 99%
“…Passow's (2012) review of competency studies across engineering disciplines found that 13 of the 19 studies published since 1990 included a balance of technical and professional competencies. Similarly, an earlier study of high-performing Australian graduate engineers by Scott and Yates (2002) found that a range of emotional intelligence capabilities (Goleman 1998), such as being able to contribute effectively to team-based projects, understanding one's strengths and weaknesses, and a willingness to persevere, were significant predictors of success. Increasing need for these broader professional competencies has prompted calls for restructuring for greater breadth in engineering education (King 2012;Lohmann, Rollins, and Hoey 2006;Sheppard et al 2008) and enhancing existing methods of teaching social skills (Emilsson and Lilje 2008), for example, the addition of leadership development programmes to undergraduate engineering curricula (Khattak, Ku, and Goh 2012) and for employees in this area (Martin et al 2005), especially for those in management roles, which itself requires ongoing development (Boyatzis and Kolb 1999;Fasano 2011).…”
Section: Competenciesmentioning
confidence: 79%
“…However, key requirements of EAM roles at various levels within the organisation across different sectors within the industry remain poorly defined and academic research is still relatively rare (Hyland, Murphy, and Salomone 2009) and subject to limitations (Trevelyan and Tilli 2007). Despite a lack of research on professional competencies in the specific area of EAM, more general research on engineers tends to highlight the importance of professional competencies in this broad area (Passow 2012;Scott and Yates 2002). However as previously stated, no work identifies the relevance of specific professional competencies within the specific EAM field.…”
Section: Introductionmentioning
confidence: 99%
“…This equates well with the stated needs of practitioners. Practitioner-based studies (Lee, 2004;Lethbridge, 2000;Trauth, Farwell, & Lee, 1993) and in the Australian context (Scott & Yates, 2002;Snoke & Underwood, 1999;Turner & Lowry, 2003) assist us in building a profile of a practicing IT professional. teaching software Freed (1992) coined the term "relentless innovation" to describe the capacity to invent and implement new ideas that will impact every facet of life.…”
Section: Practicing Softwarementioning
confidence: 99%